Facile Synthesis of Monodispersed α-Ni(OH)2 Microspheres Assembled by Ultrathin Nanosheets and Its Performance for Oxygen Evolution Reduction - Yu, Juan; Pan, Shencheng; Zhang, Yongxing; Liu, Qinzhuang; Li, Bing (Frontiers in Materials, 2019)
Electrocatalytic water splitting is an efficient route to generate renewable energy sources, in which the noble metal materials are usually used as electrocatalysts. But the high price and scarcity of these catalysts impede their large-scale applications. Ni-based materials are considered to be the most suitable catalytic materials to substitute these noble metal materials. In this paper, the monodispersed α-Ni(OH)2 microspheres assembled by ultrathin nanosheets were synthesized by a facile solvothermal method. This method was surfactant-free and no any precipitator was used. The as-obtained products were well characterized by X-ray diffraction (XRD), field emission scanning electron microscope (FESEM), transmission electron microscope (TEM), thermal gravimetric (TG) analysis, and X-ray photoelectron spectroscopy (XPS). The results of N2 adsorption/desorption isotherm indicate that the BET surface area of the products was 169.94 m2g-1, and the pore-size distribution centered at 3.5 nm. Then, the electrochemical properties were evaluated by linear sweep voltammetry (LSV) in 1 M KOH. At a current density of 10 mA cm2, the overpotential for the α-Ni(OH)2-MS is 320mV, and the Tafel slope is 98.7 mV dec-1, indicating its excellent reaction kinetics for an efficient catalyst toward oxygen evolution reaction (OER).